ANALISIS PERTANGGUNGJAWABAN TINDAK PIDANA KORUPSI AKIBAT KERUGIAN BUMN BERDASARKAN DOKTRIN BUSINESS JUDGEMENT RULE (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 34/PID.SUS-TPK/2019/PT.DKI) - Desiana, Felina; Hutabarat, Rugun Romaida (Fakultas Hukum Universitas Tarumanagara, 2021)
State-Owned Enterprises (SOEs) in the form of Limited Liability Companies and run by a board of directors and their ranks do not cover the possibility of losses in running the company. If the board of directors takes a decision that harms the company, it will be considered to fulfill the elements of Article 2 paragraph (1) of the Law on the Eradication of Corruption. Business Judgement Rule is one of the doctrines that exist in business law to protect directors and their ranks in legal liability for business decisions they take. The Business Judgement Rule arises as a result of the implementation of fiduciary duties by a board of directors. The Board of Directors is required to take full responsibility for the management of the company, in the interests of the company. In carrying out its duties the board of directors is often faced with business decisions that are not in accordance with the agreed business strategy. As in the Supreme Court's Decision 34/PID. SUS-TPK/2019/PT. DKI, a state-owned company board of directors of PT Pertamina is said to be found guilty of corruption offences due to the harm to the state's finances amounting to Rp. 568,066,000,000 as a result of the acquisition or investment in BMG Australia. Thus, the doctrine of Business Judgement Rule should be applied as long as the board of directors can prove the business decisions taken in good faith, and prudence and not enrich themselves.